The correlation between formal education and knowledge of used cooking oil management at Kampung Tersenyum society in South Jakarta - Diputra I Gede Yuda Marta; Sunardi; Siyaranamual Martin Daniel (E3S Web of Conferences, 2024)
The phenomenon of used cooking oil collection at Kampung Tersenyum in South Jakarta has not been optimal. According to the data, there are only 36 sub-districts out of 65 sub-districts in South Jakarta that have been monitored to collect used cooking oil in the period October 2019 – June 2020. This research aims to analyze the knowledge of used cooking oil management in Kampung Tersenyum Society, South Jakarta. This research used a quantitative descriptive method. The population in this research is the residents of Kampung Tersenyum, South Jakarta. The sampling technique in this research was carried out with a purposive sampling method of 60 respondents. Data collection techniques used observation and interviews with questionnaires. Data analysis used percentage descriptive techniques. The results of the research showed that the last formal education majority of the society is at the high school level. The knowledge of used cooking oil management in South Jakarta is in the high category. From the results of the analysis, it was found that there is a correlation between formal education that has been taken with waste management knowledge which is the majority of elementary and junior high school education are knowledgeable in the category tends to be low, while the majority of education at the senior high school, bachelor,and master levels are knowledgeable in the high category.